1997
DOI: 10.1200/jco.1997.15.2.466
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary leukemia adversely affects hematologic complete remission rate and overall survival in patients with t(8;21)(q22;q22): results from Cancer and Leukemia Group B 8461.

Abstract: Patients with t(8;21) and EML have a low CR rate and overall survival. An aggressive local and systemic induction therapy should be considered for this patient subset. The effectiveness of HDAC intensification in t(8;21) patients with EML is uncertain and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
4
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(165 citation statements)
references
References 0 publications
3
146
4
8
Order By: Relevance
“…Byrd et al [10] reported that CD56 expression that was associated with a high incidence of extramedullary manifestations led to poor clinical outcomes in AML with t(8;21) [7,11,20,24]. We only had two patients with extramedullary leukemia at the time of diagnosis and did not evaluate the relationship between CD56 expression and adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Byrd et al [10] reported that CD56 expression that was associated with a high incidence of extramedullary manifestations led to poor clinical outcomes in AML with t(8;21) [7,11,20,24]. We only had two patients with extramedullary leukemia at the time of diagnosis and did not evaluate the relationship between CD56 expression and adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD56 is one of the most adverse risk factors in patients with AML [5][6][7]. Although CD56 expression in AML with t(8;21) has been associated with extramedullary manifestations [8][9][10][11][12] and multidrug resistance [13,14], its clinical and prognostic significance has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although specific situations exist in which the presence of myeloid sarcoma has little effect on outcome, in general it heralds a poor prognosis. 5,[49][50][51][52] Sites of involvement vary depending on the exact underlying disorder, age of patient and the presentation (eg preceding or concurrent with systemic disease). The tumors consist of populations of blasts, but mixtures of cell types are seen in the more differentiated subtypes.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Among these are certain secondary cytogenetic aberrations, leukocytosis, CD56 expression and extramedullary manifestations. Review of the literature found that some suggested indicators, most notably CD56 9 and extramedullary involvement, 10 were identified in a single or relatively small studies; others were based on the patients treated with different protocols [11][12][13][14] or included secondary leukemia, 15 rendering it difficult to compare and draw consistent conclusions. This is particularly true regarding implications of additional cytogenetic aberrations.…”
mentioning
confidence: 99%